Living across borders: The everyday experiences of Moroccan and Brazilian transmigrants in Belgium. Issue 1 (1st April 2015) - Withaeckx, Sophie; Schrooten, Mieke; Geldof, Dirk
Based on research amongst Brazilian and Moroccan temporary residents of the cities of Brussels and Antwerp (Belgium), this article engages with the changes in and current methodological approaches to migration studies. By demonstrating how the trajectories of many contemporary migrants are marked by ongoing mobility, it further complicates previous linear and unidirectional models of migration to move beyond a classical and potentially deterministic model of studying migrant trajectories. The authors illustrate how many contemporary migrants come and go, not always being sure how long they will stay in the different stopovers on their trajectories, when they will stop migrating or where they will eventually settle. Because of the temporality of their residence, many of these so-called 'transmigrants' are not only faced with the same problems and challenges as other migrants, arriving newly in another country and rebuilding social networks, but are additionally confronted with a number of risks that are related to their mobile lifestyle. Although globalization and the porosity of nation state borders facilitate transmigration, they result in juridical and practical complexities, reflected in transmigrants' everyday struggles. The authors explore these struggles and the difficulties and opportunities transmigrants encounter when they turn to their (transnational) networks to ask for support. Transmigrants' social life is not only oriented towards their country of residence, but consists of complex networks beyond boundaries. Through visits, telephone calls and the use of social media, many transmigrants create, sustain and (re)discover transnational as well as local social networks. While many address their transnational networks to partly alleviate their needs, the development of local networks still appears as indispensable.